2020
DOI: 10.1007/978-3-030-50743-5_10
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Algorithms for Quantum Annealers with Chimera and Pegasus Connection Topologies

Abstract: We propose two new algorithms -Spring-Based MinorMiner (SPMM) and Clique-Based MinorMiner (CLMM) -which take as input the connectivity graph of a Quadratic Unconstrained Binary Optimization (QUBO) problem and produce as output an embedding of the input graph on a host graph that models the topology of a quantum computing device. As host graphs, we take the Chimera graph and the Pegasus graph, which are the topology graphs of D-Wave's 2000 qubit (first introduced in 2017) and 5000 qubit (expected 2020) quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…4. Since the embedded problems are represented by near complete graphs, CLMM is the best performer, whereas SPMM has inferior performance, as expected based on [31].…”
Section: Minor-embedding Of Mimo ML Decodingsupporting
confidence: 54%
See 1 more Smart Citation
“…4. Since the embedded problems are represented by near complete graphs, CLMM is the best performer, whereas SPMM has inferior performance, as expected based on [31].…”
Section: Minor-embedding Of Mimo ML Decodingsupporting
confidence: 54%
“…In order to embed larger QUBO problems that supersede the limitations of CLIQUE, we use two heuristic approaches that aim to yield higher qubit utilization. Clique-Based MinorMiner (CLMM) and Spring-Based MinorMiner (SPMM) [31] work by finding initial chains of qubits which can be passed to MM as a parameter in hopes of finding better final embedding using these as starting points. CLMM finds initial chains using CLIQUE, which results in the near uniformity of chains.…”
Section: B Minor-embedding Methods With Extended Heuristicsmentioning
confidence: 99%
“…Meanwhile, on the physical device (whose graph is not perfect and lacks several quantum bits and couplings), we were able to embed only three out of the four cases (case 3, with the highest number of conflicts, could not be embedded). We expect that such obstacles will become less restrictive as new embedding algorithms are being developed for both the current Chimera topology and the newest D-Wave Pegasus; see [86,87]. Therefore, it is not unreasonable to expect that the range of problems that can be embedded so that they can be solved on physical hardware will substantially increase in the near future.…”
Section: Initial Studies On the D-wave Advantage Machinementioning
confidence: 99%
“…Using the minorminer feature "f ind clique embedding()" that uses heuristics from Ref. [88,89] to adapt the optimal embeddings to broken graphs, we found that a per n optimization via full clique embeddings at each n produced immeasurably high TTS after n > 32, even with the use of "V irtualGraphComposite()", an advanced method for tuning logical qubits for a particular embedding. (This method involves correcting the flux biases of the physical qubits that are skewed due to extended-range ferromagnetic couplings used to form logical qubits.)…”
Section: D-wavementioning
confidence: 99%